RISK FACTORS FOR THE DEVELOPMENT OF PATHOLOGICAL PROCESSES IN THE STRUCTURES OF THE HIP JOINT - Nasirli, D.A. (World of Medicine and Biology, 2022)
The study included 160 patients with coxarthrosis of the III-IV radiological stages aimed at a total hip replacement for the period 2015–2018. Several variants of the course of the disease were identified, taking into account the age factor (group I), the post-traumatic factor (group II), the metabolic factor (group III) and the polyethological nature of the process (group IV). The number of patients in each group was 40 people. Upon admission to the hospital, all patients underwent a comprehensive examination using instrumental, physical, clinical, functional and laboratory research methods. The presence of excess body weight was determined based on BMI. In the presence of an age-related risk factor, coxarthrosis manifested much later than with the development of joint pathology of post-traumatic, metabolic and poly etiological genesis. Of the somatic diseases, arterial hypertension was most often found in patients with coxarthrosis, chronic heart failure, diabetes mellitus and varicose veins of the lower extremities were somewhat less common. When analyzing the incidence of diseases of the genitourinary system, chronic pyelonephritis was diagnosed in most cases. Hyperglycemia of 17.5 %and 37.5 %, respectively, were often diagnosed in these two groups, and the fasting glucose level was 5.3±0.06 mmol/l. It should be noted that there were no disorders in the functional state of the thyroid gland in patients of the second group.